2019
DOI: 10.3389/fphar.2019.01152
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Based on Dendritic Cell-Targeted/-Derived Extracellular Vesicles—A Novel Strategy for Enhancement of the Anti-tumor Immune Response

Abstract: Dendritic cell (DC)-based anti-tumor vaccines have great potential for the treatment of cancer. To date, a large number of clinical trials involving DC-based vaccines have been conducted with a view to treating tumors of different histological origins. However, DC-based vaccines had several drawbacks, including problems with targeted delivery of tumor antigens to DCs and prolong storage of cellular vaccines. Therefore, the development of other immunotherapeutic approaches capable of enhancing the immunogenicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 134 publications
(209 reference statements)
0
83
0
1
Order By: Relevance
“…For example, DCs act in the first step of the cancer immunity cycle, eliminating tumor cells through T-cell activation [ 79 ]. As they share surface membrane components that interact with other immune cells, DC-derived EVs can potentially be engineered to act as cell-free antitumor vaccines, providing a novel immunotherapy in the fight against cancer [ 80 ]. Particularly, EVs released by DCs contain major histocompatibility complex (MHC) class I and class II molecules that are able to activate cognate T cells and promote humoral responses.…”
Section: Evs and Cancer Immunotherapymentioning
confidence: 99%
“…For example, DCs act in the first step of the cancer immunity cycle, eliminating tumor cells through T-cell activation [ 79 ]. As they share surface membrane components that interact with other immune cells, DC-derived EVs can potentially be engineered to act as cell-free antitumor vaccines, providing a novel immunotherapy in the fight against cancer [ 80 ]. Particularly, EVs released by DCs contain major histocompatibility complex (MHC) class I and class II molecules that are able to activate cognate T cells and promote humoral responses.…”
Section: Evs and Cancer Immunotherapymentioning
confidence: 99%
“…In addition to NK-EVs, the anti-tumor effect of DCderived EVs (DC-EVs) for immunotherapy of cancer is under investigation in clinical trials (110). DCs are professional APCs which present antigen material to T lymphocytes activating an antigen-specific T-lymphocyte immune response.…”
Section: Ev Applications In Promoting Gvl and In Preventing Disease Rmentioning
confidence: 99%
“…Significant success in the treatment of tumors by DC-EVs has been achieved in murine models and in human cell lines. Other strategies using tumor-derived EVs to deliver antigens to DCs and stimulating GvL are under investigation (110).…”
Section: Ev Applications In Promoting Gvl and In Preventing Disease Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding EVs' application as cancer therapeutics, it basically differs from conventional approaches, i.e., molecular targeting drugs and chemotherapy. Referring to native EVs, a huge number of in vivo and in vitro studies have been reported [28][29][30][31][32][33][34]. In details, three main approaches in cancer treatment through native EVs can be identified: the inhibition of EVs production [35][36][37], the eradication of circulating EVs, and finally the reduction of EV uptake [38,39].…”
Section: Introductionmentioning
confidence: 99%